Abiraterone acetate and its use in the treatment of metastatic prostate cancer: a review. (February 2018) - Caffo, Orazio; Veccia, Antonello; Kinspergher, Stefania; Maines, Francesca
Abiraterone acetate, which targets enzymatic complexes playing a central role in steroidogenesis, demonstrated to increase survival significantly in both chemo-naive and docetaxel pretreated, becoming one of the drugs of choice for metastatic castration-resistant prostate cancer. More recently, this agent in combination to androgen deprivation therapy demonstrated to be efficacious also in metastatic castration-sensitive prostate cancer. The present review is aimed to outline the clinical development of abiraterone acetate, the pivotal trials which led to its approval for the clinical practice, new evidence about its efficacy in metastatic castration-sensitive prostate cancer, its place in the therapeutic landscape of prostate cancer and future directions of development.